ERS syllabus for postgraduate training in respiratory infections: a guide for comprehensive training. Issue 4 (December 2018) - Aliberti, Stefano; Farr, Amy; Tabin, Nathalie; Blasi, Francesco; Torres, Antoni; Woodhead, Mark; Migliori, Giovanni Battista; Sotgiu, Giovanni; Dimopoulos, George; Chalmers, James D.; Ringshausen, Felix C.; Loebinger, Michael R.; et al.
Respiratory infections, including tuberculosis, represent one of the leading causes of morbidity and mortality across the world. They represent the deadliest communicable diseases causing 3.0 million deaths worldwide in 2016 [1]. The burden of respiratory infections can be unbearable for some health systems: they represent one of the most common reasons for doctor visits, regardless of age and sex [2]. ERS has developed a syllabus for postgraduate training in respiratory infections to guide programme designers http://ow.ly/xJ0R30m8CYB